The Use of Maxims (al-Qawāʿid al-Uṣūliyyah wa al-Fiqhiyyah) in Legal Argumentation of Sharia Economic Court Decisions in Indonesia - Muhammad Taufiki; Rokani Darsyah; Mahmud Ridha (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
All sharia economic court decisions in Indonesia are supposed to include sharia principles as the basis for adjudicating the case. Therefore, the judges must be able to understand the legal norms of sharia economics. This study aimed to explore how fundamentalistic maxims (al-qawāʿid al-uṣūliyyah) and jurisprudential maxims (al-qawāʿid al-fiqhiyyah) as parts of sharia economic legal norms or sharia principles were used by judges as legal argumentation in court decisions. We analyzed 384 court decisions categorized as sharia economic cases on the Indonesian Supreme Court website from April 20, 2016, to April 20, 2020, and set them as a universe of cases. Each decision that contained the maxim (qāʿidah) in its legal consideration was selected as relevant case sample and was then analyzed to find how the maxim was used as legal argumentation to respond to a petition and/or demurrer. Then, we found 15 legal maxims from 28 legal argumentations of 14 decisions (3.65% of the universe of cases). In general, the use of those maxims as legal argumentation has already conformed to their conventional usage with a few notes related to specific legal findings (rechtsvinding) in sharia economic cases.